A novel control for MDF continuous hot-pressing accurate tracking: adaptive fuzzy approach. (2019) - Zhu, Liangkuan; Zhou, Yugang; Wang, Zibo; Liu, Yaqiu
In order to guarantee slab thickness precision of Medium Density Fibreboard (MDF), an adaptive fuzzy Dynamic Surface Control (DSC) was investigated. Firstly, a mathematical model for hydraulic servo system of the continuous hot-pressing machine with input saturation was proposed, and the auxiliary system was introduced to compensate the effect of input saturation. Due to the uncertain function in the model, a fuzzy logic system was introduced to approximate it. Subsequently, a slab thickness tracking controller with less complexity was developed with the help of the DSC approach. Simultaneously, an on-line adaptive law was applied to estimate the adjustable parameter vector in the fuzzy system. Finally, experimental results validated that the proposed method can ensure the MDF slab thickness precision in the hot-pressing process.